Transformasi Perpustakaan Berbasis Inklusi Sosial di Perpustakaan Daerah Kabupaten Berau - Aisyah, St. Nur; Mulyadi, Irvan; Ahmad, La Ode Ismail (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study aims to describe the transformation of the Berau District Public Library based on social inclusion and to identify the challenges faced during this transformation. This study uses a qualitative method with managerial, pedagogical, and juridical approaches. Data were collected through observation, in-depth interviews with the Head of the Office, the Head of Development Division, and librarians, as well as documentation. Data analysis was conducted through three stages: data reduction, data presentation, and drawing conclusions. The results show that after undergoing transformation, the Berau District Library experienced an increase in services, collections, and literacy-based activities, including community training programs. However, internal challenges such as limited facilities and human resources, external challenges including lack of stakeholder support and geographical access issues, and technical challenges such as limited infrastructure and library management systems were identified. The study implies the need for sustainable strategies to strengthen inclusive services and develop facilities that meet user needs.